Book Review of “A Guide to the World of Dreams: An Integrative Approach to Dreamwork” - Pedersen, Hanne Fogh (Canadian Journal of Counselling and Psychotherapy, 2018)
In his book, Ole Vedfelt describes dreams as an inexhaustible creative resource which, throughout life, proactively contributes to the inner balance of the personality. He begins with an overview of psychological and natural scientific knowledge of dreams and dreamwork today and introduces a theory of complexity for the integration of this knowledge. Substantiated by the relevant research, he delineates ten core qualities of dreams and illustrates these with practical dreamwork examples. Finally, the book has a manual for work with the core qualities of dreams in different settings and for different levels of expertise, such as in psychotherapy, counselling, and self-help.